Archaeological applications of spectroscopic measurements. Compatibility of analytical methods in comparative measurements of historical Polish coins. (March 2019) - Gójska, A.M.; Miśta-Jakubowska, E.A.; Banaś, D.; Kubala-Kukuś, A.; Stabrawa, I.
Graphical abstract: Highlights: The archaeological application of spectroscopic techniques is presented. The elemental composition of selected historical Polish coins were obtained. ED-XRF (made in NCBJ) results were compared to commercial WD-XRF, SEM-EDX, XRD. Good agreement between different analytical values were obtained. Abstract: The ED-XRF (energy-dispersive X-ray fluorescence) compact system was used to analyze selected Polish historical coins. The compact X-ray tube developed in the National Centre for Nuclear Research (NCBJ) was used as an X-ray source in the system designed for the ED-XRF studies. The XRF spectra were recorded with the Amptek SDD spectrometer. The elemental compositions of the coins have been determined using above mentioned system and the results were compared to those obtained with WD-XRF method. Other techniques such as SEM-EDX and XRD were also included into this work for comparison. The experimental data show that the X-ray system with transmission type X-ray tube with silver anode operating at 50 kV/30 µA which was developed in NCBJ together with the Amptek SDD spectrometer is an effective tool for chemical composition analyze of historical coins and can be successfully used in archaeometry.